Decision Making in the Real World: Unpacking the Black Box of the Decision Process for Youth Violence - Gibbs, Carole (Crime & delinquency, 2024)
Criminologists typically test rational choice theory by examining the relationship between one aspect of decision making—the perceived costs and benefits of crime—and the likelihood of crime, primarily using (experimental) surveys that lack consideration of the neighborhood context. Building on decades of research in the risk and decision sciences, the current study utilizes broader models of decision making to qualitatively examine how youth living in concentrated disadvantage make decisions during incidents of violence. Our thematic analysis of 22 in-depth interviews with youth in a midsize midwestern city indicates that the decision process regarding violence is much more complex than previously theorized.